Online Learning Challenges in Central Pandemic Virus Corona in Stai Muhammadiyah Tulungagung - Mohammad Riza Zainuddin (Tarbiyah Departement collaboration with AMCA, 2020)
The impact of preventing the spread of the corona virus was also felt in Tulungagung district, especially the Muhammadiyah Islamic University (STAI) Muhammadiyah Tulungagung which was an appeal to learn from home. Precisely the appeal is March 2020 the second week. So online learning must be implemented. Of course, in practice, challenges will be found in the implementation of online learning. So on this occasion the writer will analyze the challenges of online learning in the midst of the corona virus pandemic at STAI Muhammadiyah Tulungagung. The research approach used is descriptive qualitative. In this study the authors conclude that the challenges of online learning in the midst of the corona virus pandemic at STAI Muhammadiyah Tulungagung include: some lecturers lack mastery in using online learning media, in addition some lecturers and students have difficulty with internet network signals in their respective locations of residence, and also the use of internet quota more than before this online learning.